STATUS TAKSONOMI, DISTRIBUSI DAN KATEGORI STATUS KONSERVASI MAGNOLIACEAE DI INDONESIA - Rozak, Andes Hamuraby (Buletin Kebun Raya, 2012)
The Family of Magnoliaceae is one of the most primitive taxa in the world.Â  Knowledge of this family is essential for studies on the origin, evolution and systematics of Angiosperms.Â  There are 223 species belongs to this family in the world and 25 of them are found in Indonesia. This paper explains taxonomy, distribution, and conservation status of the family Magnoliaceae in Indonesia.